RESILIENSI GURU SEKOLAH DASAR PASCA PANDEMI COVID-19 DI JEPARA - Muh Muhaimin; Naili Rofiqoh (Tunas Nusantara, 2022)
The COVID-19 pandemic has caused many problems that must be faced by everyone, many sectors are affected by this pandemic, as well as the education sector. This study aims to describe the level of resilience of elementary school teachers during a pandemic, resilience can be said as the ability to survive and the ability to rise from adversity. The approach in this research is quantitative with quantitative descriptive analysis. The research subjects were elementary school teachers in Jepara district. The results of this study indicate that the majority of elementary school teachers in Jepara district have a fairly high level of resilience, 80% of teachers are able to survive and rise from adversity. There are five aspects of resilience, namely purpose, perseverance, equity, self-reliance and existential aloneness. The majority of elementary school teachers in Jepara have the highest level of exential aloneless from all aspects of 6.2309.Keyword: Resilience, Elementary School Teacher, Post Covid-19 Pandemic